Performance of Convergent Breeding Wheat (Triticum aestivum L.) Lines in the Lowlands - Firmansah, Habibi; Wahyu, Yudiwanti; Nur, Amin (Department of Agronomy and Horticulture, IPB University, 2024)
The development of tropical wheat in Indonesia is currently confined to the availability of wheat’s optimal environments in the highlands. Wheat competes with major highland crops, such as vegetables, which also have high economic values. Despite this, the demand for wheat in Indonesia remains high, whether in the form of wheat flour, wheat meal, or oats. Wheat breeders are actively working to create various crossbreeds so that wheat can adapt and perform effectively in lowland areas. The convergent breeding method is one of the strategies employed to produce genotypes with superior performance. Convergent breeding enhances genetic diversity by incorporating superior traits from all parent plants. The breeding results expedite the emergence of genetic combinations between selected parents. This method involves combining several parent varieties with various traits, with the hope that their offspring will inherit all the characteristics of the crossed parents. Our study with wheat convergent breeding has reached the F6 generation, and in this current study we evaluated the performance of each observed trait in different environments, with the goal of determining the levels of homogeneity and homozygosity. The study utilized a randomized complete block design with three replications, and the crops were planted in various locations. The planting locations selected were those that are >1000 m above sea level (asl), and at a lowland of ± 250 m asl. Wheat performance based on stomatal characteristics showed a reduction in the lowland, which indicates a response to climatic conditions in a particular environment. The higher the environmental temperatures, the smaller the stomatal size, which reduces plant water loss. Noteworthy findings include the tallest plant in CBF-6. CAMN23(265), the highest number of tillers in CBF-6. CAMN233 and CBF-6.CAMN8(4), the largest flag leaf area in CBF-7.CAMN60, and the highest 100-seed weight, as well as overall yield in CBF-7.CAMN119. An analysis of the lowland sensitivity index identified ten moderate genotypes that could potentially adapt well and achieve optimal yields.